EVALUATING THE CLINICAL INTEGRATION OF THE MEDSCAPE APP AMONG HEALTHCARE PERSONNEL IN PAKISTAN (The Research of Medical Science Review, 2025)
Objectives: This study aimed to assess the prevalence and patterns of Medscape app usage among healthcare professionals, medical students, and AI conference attendees in Pakistan, identify barriers and facilitators to its clinical integration, and evaluate its perceived effectiveness in supporting clinical decision-making.Method: A cross-sectional survey was conducted with 351 participants from POF Hospital, WAH Medical College, and an AI conference in Pakistan. Data were collected using a structured questionnaire based on the Technology Acceptance Model (TAM), employing online (Google Forms) and offline (paper-based) methods. The questionnaire included Likert-scale, multiple-choice, and binary response questions, pilot-tested for reliability (Cronbach’s alpha > 0.7). Quantitative data were analyzed using SPSS, with descriptive statistics (frequencies, percentages, means, standard deviations), inferential statistics (ANOVA, t-tests), and Pearson correlations, setting a p-value threshold of <0.05.Result: Of the 351 participants, 58.1% used Medscape, primarily for clinical guidelines (40.8%) and drug interaction checkers (28.0%). Barriers included time constraints (33.3%), lack of training (25.2%), and technical issues (16.0%), while facilitators were perceived reliability (73.8%) and ease of navigation (50.4% rated easy/very easy). Medscape moderately improved clinical decision-making (Mean=2.74, SD=0.70) and reduced diagnostic uncertainty (Mean=2.94, SD=0.79), with nursing professionals showing greater uncertainty reduction than medicine professionals (p=0.032).Conclusion: Medscape demonstrates moderate integration in Pakistan’s healthcare system, with significant potential to enhance clinical decision-making. Addressing barriers like training gaps and technical issues through targeted interventions could promote broader mHealth adoption, informing strategies for digital health integration in resource-constrained settings.